2012
DOI: 10.1007/s00590-012-0966-3
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal alignment of the cervical spine after neck injury

Abstract: The normal sagittal alignment of the cervical spine is lordotic and is affected by the posture of the head and neck. The question of whether loss of cervical lordosis is the result of muscle spasm after injury or a normal variation, and the clinical significance of such changes in sagittal profile of the cervical spine has been an issue of several studies. The purpose of this paper is to study the incidence of normal cervical lordosis and its changes after neck injury compared to the healthy population. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The standing or sitting position of the patient, pelvic tilt, and the position of the head during filming may affect the cervical spinal curvature (4,8,20). For this reason, in order to get an accurate measurement, the patient must be filmed in neutral posture and the patient's head must also be in a neutral position (20). Therefore, in our study, we preferred using the tangent method in the global evaluation of the cervical spinal angle, evaluating the results with two specialists who reached a consensus and filmed with the standard X-ray method in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The standing or sitting position of the patient, pelvic tilt, and the position of the head during filming may affect the cervical spinal curvature (4,8,20). For this reason, in order to get an accurate measurement, the patient must be filmed in neutral posture and the patient's head must also be in a neutral position (20). Therefore, in our study, we preferred using the tangent method in the global evaluation of the cervical spinal angle, evaluating the results with two specialists who reached a consensus and filmed with the standard X-ray method in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This has led some practitioners to place emphasis on the restoration of the lordotic curve as an important outcome measure for their treatment [ 8 , 11 , 30 ]. However, other researchers have suggested that a lack of lordosis is a normal variant and therefore not a cause of symptoms for neck pain [ 14 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the time frame, it seems reasonable to suggest that positioning may not have been standardised across time. In addition, others [ 13 18 ] found no association between lordosis and neck pain, and in a literature review Gay [ 16 ] concluded that the curve of the cervical spine had little prognostic significance. Further, a more recent systematic review concluded that an association between cervical lordosis and spinal pain was not supported by the epidemiological evidence, albeit much of the research reviewed was found to be of low methodological quality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies indicated that changes in spinal curvature were not associated with a clinically significant injury. 54,111 For example, Beltsios and colleagues 8 indicated that presence of abnormal curvatures was not more common following neck injury and that abnormal curvatures should be considered normal variants and not pathological alignment. Grob and colleagues 35 found no association between any clinical characteristics of neck pain and cervical spine curvature.…”
Section: Cervical Spinal Posturementioning
confidence: 99%